Homosexualidad masculina y lesbianismo en la psicología china: revisión sistemática entre 2012 y 2016 (2021)
To identify the study and the approach that Chinese psychology carries out on homosexuality and lesbianism, we completed a systematic review of the published bibliography between 2012-2016. We have done the search in six databases: BVS, Dialnet, PsycINFO (PsycNET), Scopus, Web of Science and CNKI (中国知网). As result, we found 240 articles: 202 from the mainland of China, 30 from Hong Kong, and 12 from Taiwan. We have analyzed the used languages, the amount of publication in each year, the areas of psychology in which they were published and the topics of the published investigations have been organized into twelve categories. Based on the results, we present a discussion on the constructed pathologization of the homosexual population, the invisibility of the female homosexual population, the hegemony of the English language and the effect of the censorship of the scientificpublication.